2018
DOI: 10.1016/j.eurpsy.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of borderline personality features in the relationship between childhood trauma and psychotic-like experiences in a sample of help-seeking non-psychotic adolescents and young adults

Abstract: Objective:Psychotic-like experiences (PLEs) often occur across different non-psychotic disorders in adolescent and young adult population and are related to early trauma. However, the mechanisms of how exposure to early trauma shapes the risk of PLEs are unclear. In our study, we investigated whether borderline personality features and further non-psychotic symptoms, i.e. factors related to both PLEs and childhood trauma, may mediate the relationship between childhood trauma and PLEs.Methods:Two hundred inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…The association between early traumatic experiences and PLEs has been shown both in population-based studies [8], as well as among help-seeking adolescents and young adults [9]. It has been shown that even after controlling demographic factors and comorbid mental disorders, the relationship between traumatic life events and PLEs is fairly significant with odds ratios ranging from 3 to 11 as presented by a recent meta-analysis [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between early traumatic experiences and PLEs has been shown both in population-based studies [8], as well as among help-seeking adolescents and young adults [9]. It has been shown that even after controlling demographic factors and comorbid mental disorders, the relationship between traumatic life events and PLEs is fairly significant with odds ratios ranging from 3 to 11 as presented by a recent meta-analysis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies showing the association between early trauma and PLEs/psychosis, the mechanisms by which trauma influences the development of psychotic symptoms remain unclear. Several models focusing on psychological and biological mechanisms have been suggested so far and various mediation models have been proposed linking childhood and adolescent trauma with PLEs in nonclinical samples, including different variables such as: perceived stress, external locus of control, negative self-schemas, negative other-schemas [8], cognitive biases [30][31][32], resilience [32], dissociation [8,33], depressive symptoms [34], selfdisturbances [30,31,35], insecure attachment styles [30], borderline personality features [9], and aberrant salience [36].…”
Section: Introductionmentioning
confidence: 99%
“…Many reported the term as belonging outside of psychotic disorders . Definitions included ‘psychotic symptoms experienced by a part of the healthy population without frank disorder’, ‘subclinical psychotic phenomena like perceptual anomalies and delusion‐like experiences in the absence of manifest psychotic illness’, and ‘mild and/or transient forms of the experiences and symptoms reported by schizophrenia patients’ found among ‘psychosis‐prone individuals’ . Psychotic experiences and PLE have similarly been considered as psychotic symptoms ‘in an attenuated form’, and ‘experiences hallucinatory or delusional in nature but with reality testing remaining intact.’ PLE are also defined as ‘mild versions of psychotic symptoms’ .…”
Section: Resultsmentioning
confidence: 99%
“…iPQ-16 is a 16items self-report instrument that explores the presence/absence of 16 PLEs, including perceptual aberrations/hallucinations, unusual thought content/delusions, and two negative symptoms, and their associated psychological distress score on a four-point likert scale ranging from 0 to 48. Although the iPQ-16 was originally designed as a screening tool for individuals at Ultra-High Risk in help-seeking populations, several studies have used this instrument in non-help-seeking samples as a measure of PLEs (15,(23)(24)(25). We used the distress scale as recommended by Savill et al, (26) for non-help-seeking populations, using a cut-off of ≥11 as recommended by Pelizza et al (27) according to the Italian field test.…”
Section: Measures Prodromal Questionnaire-16 Italian Versionmentioning
confidence: 99%